On the existence of a surface in the pseudo-Euclidean space with given Grassman image - Grechneva, M. A.; Stegantseva, P. G. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We study the properties of submanifolds of the Grassmanian manifold of the four-dimensional pseudo-Euclidean space andalso the Grassman image of a surface in this space. The theorem on the existence of a surface in the pseudo-Euclideanspace with the given Grassman image is formulated and proved.